1997
DOI: 10.1021/jf960558j
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity of Corn Bran Cell-Wall Fragments in the LDL Oxidation System

Abstract: The antioxidant activity of feruloyl arabinose, a model substance of cereal cell-wall fragments, in the LDL autoxidation system by CuSO 4 and its absorption were studied. Ferulic acid added as free acid showed little suppressive effect on LDL oxidation. However, ferulic acid sugar esters showed a positive effect. This fact indicated that affinity of LDL particle and free or bound ferulic acid is important for the suppressive effect. The HPLC analysis showed that in rats administered feruloyl arabinose, two pea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 36 publications
1
51
0
Order By: Relevance
“…In order to avoid excess levels of free FA in the wort, inactivation of ferulic acid esterase in commercial enzyme preparations is recommended. The esters of FA obtained after enzymic degradation of arabinoxylans (FA-Araf and FA-Araf-XylpXylp) exhibit a higher antioxidant activity against low density lipoproteins (LDL) than free FA 39,40 . The form of FA in beer (free or bound) also affects the flavour stability of this beverage.…”
Section: Resultsmentioning
confidence: 99%
“…In order to avoid excess levels of free FA in the wort, inactivation of ferulic acid esterase in commercial enzyme preparations is recommended. The esters of FA obtained after enzymic degradation of arabinoxylans (FA-Araf and FA-Araf-XylpXylp) exhibit a higher antioxidant activity against low density lipoproteins (LDL) than free FA 39,40 . The form of FA in beer (free or bound) also affects the flavour stability of this beverage.…”
Section: Resultsmentioning
confidence: 99%
“…Apart from phenolic acids, presence of sugars with > C=O (uronyl/acetyl) groups and degree/nature of polymerization impart strong antioxidant activity to the polysaccharides. The ferulic acid present in cereals exhibited strong antioxidant activity in its bound form and thus it need not get digested and be released in the colon through the action of microflora to exert its activity (Ohta et al 1994(Ohta et al , 1997Rao and Muralikrishna 2006).…”
Section: Structural and Functional Features Of Nspmentioning
confidence: 99%
“…Feruloyl oligo-and polysaccharides are known to exhibit antioxidant activity in vitro (Ohta et al, 1994;Ohta et al, 1997). Because ferulic acid, a major bound phenolic acid, is known to exist as ester-linked mainly to arabinoxylan, arabinoxylan containing phenolic acid is considered to be the antioxidative component of the WS obtained in this study.…”
Section: Resultsmentioning
confidence: 86%
“…Therefore, further study is needed to clarify the changes in free and bound phenolics during processing. Ferulic acid exhibits an antioxidative activity (Sahidi et al, 1992;Ohta et al, 1994;Castelluccio et al, 1995;Ohta et al, 1997;Andreasen et al, 2001;Liyana-Pathirana and Shahidi, 2006) and has recently been reported to show depressor, anti-tumor, and anti-Alzheimer's activities (Mori et al, 1999;Yan et al, 2001;Suzuki et al, 2002;Mamiya et al, 2004). Therefore, rolled oats may also exhibit these effects.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation